Streptococcal toxic shock syndrome with acute respiratory distress syndrome following adenotonsillectomy in a child: a case report - Yang, Wenhai; Lai, Zhijun; Li, Henian; Ma, Keze (Frontiers in Pediatrics, 2025)
This article reports a case of an 8-year-old child who developed Streptococcal Toxic Shock Syndrome (STSS) and Acute Respiratory Distress Syndrome (ARDS) following adenotonsillectomy, summarizing the diagnostic and treatment process. Preoperative blood tests, CRP levels, and chest x-rays of the child showed no abnormalities. However, within two hours after surgery, the patient exhibited high-grade fever, dyspnea, and altered mental status, rapidly progressing to shock and ARDS. Although shock was not diagnosed promptly in the early stage, leading to non-standardized fluid resuscitation therapy, blood pressure and heart rate eventually stabilized after adjusting the fluid resuscitation protocol and combining vasoactive medications. The diagnosis of STSS was ultimately confirmed based on sputum bacterial culture from endotracheal intubation and targeted next-generation sequencing(tNGS) results. STSS manifests with sudden onset and rapid progression clinically. It is often misdiagnosed in the early stages, resulting delayed treatment of shock and consequently an extremely high mortality rate.